Out of range eaudiobook - Box, C. J. (Joe Pickett, 2008)
C. J. Box's best-selling Joe Pickett novels have earned him a spot on every serious suspense fan's shortlist of favorites. The tightly constructed Out of Range brings game warden Joe to a new, remote beat in Wyoming's vast countryside to investigate the suspicious death of the previous warden. ". if anything, Box is getting better. Recommended for practically everybody." -Booklist, starred review